HUBUNGAN PERAN ORANG TUA DAN GURU DENGAN PRESTASI BELAJAR ANAK DIDIK - Siti Fatimatul Zahro; Muhammad Farid; Abdul Rouf (Arsy : Jurnal Studi Islam, 2017)
Teachers is a figure very close to the students in the school as a student at gurula study. While the parents are very close to the figure of the child, the parent is given the moral and financial responsibility. This study aims to determine how much the relationship between the teacher 's role and the role of parents and the learning achievement of students in Islamic Primary School of Darul Ulum Doho Dolopo Madiun.This research is a quantitative study with explanatory research approach. In this study there are variables X1 (The role of teachers) and X2 (the role of a parent) with Y (achievement of learning). Methods of data collection using a questionnaire distributed to students in Islamic Primary School of Darul Ulum Doho as respondents are then processed throughpearson correlation and multiple regression analysis using SPSS software 17th version.The population in this study were all students at in Islamic Primary School of Darul Ulum Doho, amounting to 144 students and 49 students of them defined as responders , especially of class V and VI classes.Based on the hypothesis test concluded that (1) there is a significant relationship (p = 0.000) between the role of the teacher and the learning achievement of students in Islamic Primary School of Darul Ulum Doho (2) there is a significant relationship (p = 0.000) between the roles of parents with learning achievement of students in Islamic Primary School of Darul Ulum Doho (3) There is a significant positive relationship (p = 0.000) together the roles of teachers and parents role of student achievement in Islamic Primary School of Darul Ulum Doho Dolopo Madiun.